2020
DOI: 10.1055/a-1324-8498
|View full text |Cite
|
Sign up to set email alerts
|

Primary obesity surgery endoluminal (POSE-2) procedure for treatment of obesity in clinical practice

Abstract: Introduction POSE-2 procedure shortens and narrows the stomach using multiple full-thickness plications in the gastric body. We studied the efficacy and safety of POSE-2 for obesity at 1-year in a real-world setting. Methods We reviewed the records of 75 patients who underwent POSE-2 at our unit. The primary outcome was to evaluate the %total body weight loss (%TBWL) at 1-year. Our secondary outcome was to assess the safety and durability. We used linear mixed model analysis. RESULTS: Forty-six patients com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Specifically, at 1 year, the patients experienced an average of 15.5% TWL, with 63% of the cohort experiencing at least 10% TWL. It is important to note that in this series, the serious adverse event (SAE) rate was 4.4%, which is substantially higher than that in the published literature for this procedure, which so far has primarily focused on patients without advanced fibrosis (31,32), likely reflecting the higher-risk patient population. This risk profile emphasizes the need to screen patients who undergo bariatric endoscopy for advanced hepatic fibrosis and a low threshold to further investigate with cross-sectional imaging and potentially direct portal pressure gradient measurement when indicated.…”
Section: Discussionmentioning
confidence: 69%
“…Specifically, at 1 year, the patients experienced an average of 15.5% TWL, with 63% of the cohort experiencing at least 10% TWL. It is important to note that in this series, the serious adverse event (SAE) rate was 4.4%, which is substantially higher than that in the published literature for this procedure, which so far has primarily focused on patients without advanced fibrosis (31,32), likely reflecting the higher-risk patient population. This risk profile emphasizes the need to screen patients who undergo bariatric endoscopy for advanced hepatic fibrosis and a low threshold to further investigate with cross-sectional imaging and potentially direct portal pressure gradient measurement when indicated.…”
Section: Discussionmentioning
confidence: 69%
“…49 The POSE 2.0 utilizes the same IOP to create multiple full-thickness interrupted plications at the level of the gastric body while sparing the fundus and has a much more favorable safety profile. 50 51 POSE 2.0 demonstrates favorable weight loss outcomes in several trials in which TBWL for patients post-POSE ranged between 15.7 and 17.3% at 6 months. 50 51 52 In a recent prospective multicenter trial, 41 subjects underwent POSE 2.0 and were assessed for weight loss and other outcomes, and were found to have %TBWL of 13.9, 17.3, and 17.5% at 3, 6, and 9 months, respectively.…”
Section: Primary Obesity Surgery Endoluminalmentioning
confidence: 96%
“…50 51 POSE 2.0 demonstrates favorable weight loss outcomes in several trials in which TBWL for patients post-POSE ranged between 15.7 and 17.3% at 6 months. 50 51 52 In a recent prospective multicenter trial, 41 subjects underwent POSE 2.0 and were assessed for weight loss and other outcomes, and were found to have %TBWL of 13.9, 17.3, and 17.5% at 3, 6, and 9 months, respectively. 50 New data from this trial show %TBWL of 15.7 ± 6.8%.…”
Section: Primary Obesity Surgery Endoluminalmentioning
confidence: 96%
“…POSE 2 is a variation of the original procedure in which plications are restricted to the gastric body. Lopez-Nava et al [62] reported superior TBWL with Pose 2 (17.8%) compared to the original Pose procedure.…”
Section: Endoscopic Tissue Appositionmentioning
confidence: 97%